Tanshinone IIA down-regulates -transforming growth factor beta 1 to relieve renal tubular epithelial cell inflammation and pyroptosis caused by high glucose. Issue 5 (2nd May 2022) - Li, Ying; Deng, Xu; Zhuang, Wenlong; Li, Yong; Xue, Hui; Lv, Xin; Zhu, Shuqin
ABSTRACT: Diabetic nephropathy (DN) is a microvascular disease caused by diabetes. Tanshinone IIA has been indicated to ameliorate streptozotocin-induced DN. This study explores the effect of tanshinone IIA on high glucose-induced renal tubular epithelial cell pyroptosis and inflammation. High glucose-stimulated HK-2 cells were used as the in-vitro model of DN and were treated with tanshinone IIA at concentrations of 1, 5, 10 μM for 24 h with the same doses of tolbutamide as the control. After tanshinone IIA treatment, HK-2 cells were transfected with pcDNA-transforming growth factor beta 1 (TGFB1) or sh-TGFB1 for 48 h. RT-qPCR was used to detect the mRNA levels of TNF-α, IL-6, IL-1β, and IL-18. Cell apoptosis and pyroptosis were detected by flow cytometry and cell immunofluorescence. Bioinformatics screening predicted that tanshinone IIA might be an effective component of Salvia miltiorrhiza Bunge (Labiatae) for the treatment of DN. Tanshinone IIA exerted a protective effect in the in-vitro model of DN by suppressing inflammation and pyroptosis via the TGFB1-dependent pathway. Tanshinone IIA inhibited high glucose-induced renal tubular epithelial cell inflammation and cell death through pyroptosis by regulating TGFB1, indicating the therapeutic potential of tanshinone IIA for DN treatment. Graphical Abstract: uf0001